The Determinant of Employee's Performance: A Systematic Literature Review - Alean Kistiani Hegy Suryana; Jati Waskito; K Kussudyarsana (Universitas Muhammadiyah Surakarta, 2025)
The purpose of this study is to analyze the determinants of employee performance. The methods used in this study are the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method and Bibliometric Analysis using Vosviewer. The data source was obtained from Scopus for the period 2015-2025. Based on the results of the literature that has been reviewed with the search results for